God Without Metaphysics: Some Thomistic Reflections on Heidegger's Onto-Theological Critique and the Future of Natural Theology - Gable, Justin (American catholic philosophical quarterly, 2021)
The Heideggerian critique of onto-theology has attained a semi-canonical status for continental philosophy of religion. But is the critique itself sound, and does it actually result in a richer philosophical and theological discourse concerning God? In this paper, I argue that Heidegger's onto-theological critique suffers from serious difficulties. First (section II) I examine the critique, summarizing and condensing the critique in its essentials. I use Westphal's fourfold criteria as a way of giving it some precision, while presenting it in relative independence from Heidegger's own account of Being. In section III, I examine the results of non-onto-theological discourse on God post-Heidegger, suggesting, using the examples of John Caputo and Richard Kearney, that Heidegger's onto-theological critique has not inspired a less problematic religious discourse. In the fourth and final section, I question the legitimacy of the critique itself. While Heidegger's critique of onto-theology has the seemingly admirable goal of rendering our discourse about God less instrumental and idolatrous, a careful analysis of the criteria themselves reveals that onto-theology either misinterprets natural theological discourse on God or subjects it to impossible requirements.